A multiplex view of leadership structure in management teams. Issue 4 (13th April 2020) - Song, Yifan; Fang, Yanran; Wang, Mo; Shi, Junqi
Abstract: In the hope of complementing the structural perspective in upper echelon research and advancing a fine‐grained understanding of dyadic leadership influence in management teams, the current study combines two types of intrateam structures—leadership network and friendship network—to create a multidimensional conceptualization of leadership structure in management teams. Specifically, we propose that management teams with a denser singular leadership network (i.e., a network consisting of many leadership ties that are not coupled with friendship ties) should have lower management team cohesion, which subsequently renders worse business unit performance. To contrast, management teams with a denser multiplex network (i.e., a network consisting of many leadership ties that are coupled with friendship ties) should have higher management team cohesion, which subsequently renders better business unit performance. Guided by structural contingency perspective, we further propose that management team task interdependence will strengthen team cohesion's positive impact on business unit performance. To test the hypothesized model, we collected team‐level social network data and multiple‐wave survey data from 697 managers nested in 148 hotels (i.e., 148 management teams) owned by a large hospitality company. We also obtained objective performance data for each hotel (i.e., occupancy percentage rate and revenue per available room per day) as the criterion measure. The data supported our hypotheses. The theoretical and practical implications of our findings are discussed.